Eduardas Volteris and the Institutionalization of Book Science in the Early 20th Century - Aušra Navickienė (Knygotyra, 2020)
Eduardas Volteris (1856‒1941) is one of the first book theorists in the Eastern European region and developer of the most important memory and higher education institutions of independent Lithuania. This article analyzes the early 20th c. phenomenon of the institutionalization of book science. It attempts to answer the question of how Eduardas Volteris contributed to establishing the very first Eastern European societies of book researchers, to consolidating the sciences of bibliography, bibliology and book science within the realm of academia, and to professionalising of book scholarship. The sources for examination of the social aspects of book science are: documents belonging to the Russian Society of Bibliology, which was active in St. Petersburg in 1899–1931, materials in scholarly serial publications on book science of the early 20th c., theoretical papers published by E. Volteris, and the results of the historical studies on the history of European book science.